KAJIAN ANALISIS TERHADAP PENYELENGGARAAN MAJELIS TA’LIM DALAM PP. NO. 55 TAHUN 2007 - Heri Rifhan Halili; Cik Na'imah; Benny Prasetiya (IMTIYAZ: Jurnal Ilmu Keislaman, 2021)
This article discusses an analytical study of the implementation of the majleis ta'lim based on PP No. 55 of 2007. As the oldest educational institution in Indonesia, the taklim assembly functions as a medium for disseminating the Islamic teachings of the guardians. As the embryo of the implementation of Islamic boarding schools and Islamic boarding schools, Majleis Taklim has a very significant function in increasing the religiosity of the Islamic ummah. The presence of government policies in PP no. 55 of 2007 concerning religious education and religious education, one of which regulates the ta'lim assembly is one of the right policies according to the needs of the community, especially Muslims. However, in its application, PP No. 55 of 2007 especially in article 21 which explains about the ta'lim assemblies need to be guarded and guarded by providing technical guidance from the government in this case winning, so that the ta'lim majlis can optimize its role in the midst of Muslims, and do not experience problems. problems that can actually hinder the development of the ta'lim assembly.